Spectrophotometry Based Oxidative Coupling Method for Determining Thymol Utilizing a Coupling Agent - Zayan, Batool Mansour; Humeidy, Israa Talib; Abdel Aziz, Mohammad Salim (Universitas Gadjah Mada, 2024)
Developing a spectroscopic approach to assess the medicinal substance thymol was one of the research's objectives. Using an oxidative coupling reaction between thymol solution and N,N-dimethyl-p-phenylenediamine dihydrochloride solution (N,N-DMPPDADH) in alkaline media with potassium periodate as an oxidizing agent, the current technology forms a blue-colored soluble product. The wavelength at which a colored product exhibits maximum absorption is 600 nm. According to Beer's law, the concentration range covered by the approach under review is 1.25–20.00 μg/mL of thymol. The specific molar absorbance value of 10725.71 L/mol cm indicates the method's sensitivity. The Sandell significance value was 0.014 μg/cm2, which represents sensitivity per unit length. The precision of the method is demonstrated to be commendable, and the low relative standard deviation value of 0.16% supports this. This method's accuracy in identifying thymol at such low quantities is demonstrated by its confirmed detection limit of 0.0124 μg/mL. The developed technique has been useful in screening thymol in pharmaceutical products, with mouthwash being the focus of particular attention. Thymol content in real-world samples was accurately determined using the approach, as evidenced by the reported 101.13% recovery rate of thymol in the examined samples.